Social and personal factors influencing the adoption of compulsive healthy eating behaviors : the mediating role of body dissatisfaction - Sousa, Maria Inês Bastos Lobato de (2022)
The purpose of this study is to investigate the effect of seven social and personal factors, namely Instagram use, fitness and health-related content, internalization, social comparisons, perfectionist and obsessive-compulsive personality traits, on body dissatisfaction and Orthorexia Nervosa. Moreover, the study also discusses the differences among Portuguese and Brazilian societies to underline potential, as the cultural role. A survey-based study with a sample of 238 respondents (138 Portuguese and 100 Brazilian) has been developed to test the proposed model, using the structural equation modelling. The data analysis shows that the main factors that influence body dissatisfaction and Orthorexia Nervosa are the internalization of beauty ideals, social comparisons (both upward and downward) and perfectionism. Body dissatisfaction mediates the path from internalization, upward and downward comparisons and perfectionism from one side and Orthorexia Nervosa on the other side. Because the results for Portugal and Brazil are identical, culture does not appear to have a substantial impact on the outcomes for this model. Finally, the thesis concludes with discussing and providing actionable managerial implications.